The psycho-social agenda in Peru: autoperception of achievements, representation of social effectiveness and social responsibility - Arenas Iparraguirre, Carlos (2009)
The main purpose is to highlight the role of social psychology in response to social demands, identify the self-perception of the achievements that own social psychologists have their profession, contrasting it with the evidence that social representations of effectiveness than objectively are present and framing this set of autopercepciones and social representations in the area of responsibility social. Using qualitative methodology (focus groups, interviews) (participatory research) explores the set of perceptions and representations from the social responsibility that you are responsible discipline psychologicosocial. How are perceived and represent the effectiveness of its work psychológicosocia and what is the relationship with the level of social representation they have been built in the course of their training académicoprofesional. The expected results are to demonstrate the effectiveness of the implementation of the social psychology in policies and social programmes versus priority social problems in Peru, i.e. the agenda and build indicators to facilite the effectiveness if such knowledge programmes in areas such as training, research and professional and theorists from the perspective of actors, social psychologists, in the various regions of the country.